2021
DOI: 10.3389/fpsyg.2021.731645
|View full text |Cite
|
Sign up to set email alerts
|

Can Yoga Boost Access to the Bodily and Emotional Self? Changes in Heart Rate Variability and in Affective Evaluation Before, During and After a Single Session of Yoga Exercise With and Without Instructions of Controlled Breathing and Mindful Body Awareness in Young Healthy Women

Abstract: Exercise is indispensable for a healthy lifestyle. Yoga exercise can have positive effects on well-being and on cardiac autonomic activity making it an ideal intervention for improving mind-body interactions and resilience to physical and mental stressors. Emotions trigger especially strong bodily and affective-cognitive responses because of their social relevance for the self and their biological relevance of mobilizing the organism for action. This study investigates whether changes in emotion processing rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
(94 reference statements)
3
4
0
Order By: Relevance
“…These findings suggest that our interventions may have been more similar than we intended them to be. This is in line with one other study comparing a short (30-minute) intervention of yoga postures with breathing techniques and mindfulness instructions to yoga postures without breathing techniques and mindfulness instructions (Herbert, 2021). Similar to our results, Herbert (2021) found no difference between the two groups on affect ratings and awareness of bodily signals.…”
Section: Strengths and Limitationssupporting
confidence: 93%
“…These findings suggest that our interventions may have been more similar than we intended them to be. This is in line with one other study comparing a short (30-minute) intervention of yoga postures with breathing techniques and mindfulness instructions to yoga postures without breathing techniques and mindfulness instructions (Herbert, 2021). Similar to our results, Herbert (2021) found no difference between the two groups on affect ratings and awareness of bodily signals.…”
Section: Strengths and Limitationssupporting
confidence: 93%
“…Interestingly, four sessions of 22 min of ergometer exercises [cycling at moderate intensity, see ( 62 )] carried out with different attentional focus (internal vs. external) at moderate intensity seem not to have differential effects on cardiovascular activity during the exercise compared to a control condition (no cycling) in a sample of healthy women, however, the self-reported attentional focus during exercise seems to influence both, the degree of exertion from the exercise and the correlations with measures of cardiac activity [see Table 4 in ( 62 )]. In contrast to the cycling exercise used in study 4, the results of study 5 ( 64 ) found significant effects on indicators of well-being after a single session of mind-body exercise (yoga). In study 5, women (all university students) performed yoga exercises either with (exercise group 1) or without controlled breathing and mindfulness instructions (exercise group 2) for 30 min.…”
Section: Resultsmentioning
confidence: 62%
“…Thirty-five percentage of the university students reported to spend between 15 and 25 h/week at the university and akin to the participants of the study 1 and study 2, the participants of the study 3 reported to be physically active only about 62.86–137.96 min/day and 15% in total did not reach the WHO recommendations. Seventy-four percentage of the all-female sample of study 5 ( 64 ) reported to spend at least once a week in regular exercise activities such as jogging, swimming, cycling, dancing, team sports, martial arts, strength training, balance, or gymnastics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations